Fault location on a series‐compensated three‐terminal transmission line using deep neural networks. Issue 6 (1st September 2018) - Mirzaei, Mahdi; Vahidi, Behrooz; Hosseinian, Seyed Hossein
Abstract : In this study, discrete wavelet transform (DWT) and deep neural network (DNN) are utilised for fault location in a series‐compensated three‐terminal transmission line. The series compensation causes challenges in fault location schemes of the three‐terminal transmission lines. The presented fault location method has been extensively tested using the SIMULINK model of a three‐terminal transmission line. Features extracted from synchronous measurements of fault currents at the three terminals using DWT are fed to the DNN. Faulted section determination and fault distance calculation are carried out using a single intelligent network simultaneously. Faulted section is determined with 100% accuracy, and the efficiency of algorithm is validated for symmetrical and unsymmetrical faults, and different values of fault resistance, inception angle, and location. The accuracy of the algorithm is acceptable for large fault resistances (above 100 Ω) and fault inception angles near zero. Total mean error for test data is 0.0458% which is much improved with respect to other similar works.